Effects of sport specific, governed, and non-controllable focal point on collegiate volleyball players? jumping performance - Bosak, A.; Sanders, R.; Nelson, H.; Lowell, R.; Feister, J. (The Journal of Strength and Conditioning Research, 2021)
Some studies have assessed factors that impact vertical jump performance in athletes, yet none have manipulated a focal point. Prior studies attempted to manipulate the target (i.e., non-controllable vs. governed focal point) that female and male above averagely fit subjects focused on to complete the jumps with a set focal point ultimately contributing to greater jumping performance. Also, a previous focal point vertical jump study utilizing fairly fit male subjects suggested that vertical jump performance increased when using a sport specific focal point. However, this sport specific focal point protocol has not been assessed using a male collegiate volleyball population where jumping as high as possible multiple times is often necessary during a game. Purpose: To determine if a sport specific focal point contributes to an increase in jumping performance compared to non-controllable (i.e., no set focal point), and a governed (i.e., set focal point) in collegiate male club volleyball players. Methods: 16 club level collegiate male volleyball players had descriptive data collected (i.e., age, HT, WT, BF%) and their reach height measured. Subjects completed a dynamic 8 minutes warmup, which avoided static movements, and then received a 4 minutes passive recovery (PR) period. Subjects then completed 3 familiarization jumps in a counter movement manner and then had another 4 minutes of PR. After the second 4 minutes PR period, subjects completed 6 jumps per each jump series with 30 seconds of rest between jumps and 6 minutes of PR between each jump series. The jump series protocol consisted of 3 separate counterbalanced jump series which included a sport specific (FPS), governed (FP), and/or non-controllable focal point (FPN). FPS, FP, and FPN were compared using ANOVA statistical procedures with significance determined at an alpha level of 0.05. Results: FPS (76.90 + 8.39 cm) was significantly different versus FP (76.20 + 8.27 cm) (p = 0.041) and FPN (76.28 + 8.17 cm) (p = 0.047). Also, there was no significant difference (p = 0.428) between FPN and FP. Conclusions: It appears that using a sport specific focal point may elicit a higher jump in collegiate male club volleyball players as compared to the jumps when the males utilized a non-controlled or a governed focal point. Further research is necessary in order to evaluate the use of a sport specific focal point on vertical jump performance with professional male volleyball players or collegiate and professional female athletes who participate in jumping sports (i.e., basketball, volleyball). Practical Application: The results of the present study suggest that when assessing the vertical jump performance of collegiate male club volleyball players it may be wise for testing administrators to suspend a volleyball in the air slightly higher than athlete's previous highest jump in order to see if this "game similarity situation" will motivate the player to jump even higher.